2023
DOI: 10.4103/jmu.jmu_2_23
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Fasciitis: An Updated Review

Wen-Che Tseng,
Yun-Chang Chen,
Tsung-Min Lee
et al.

Abstract: Plantar fasciitis (PF) is a common musculoskeletal disease. Histologic findings of patients with PF showed mainly chronic degenerative processes rather than inflammation. In addition to mechanical factors, such as repetitive stress and reduced ankle dorsiflexion, PF is also linked to rheumatologic diseases and genetic factors. Ultrasound is becoming a standard imaging technique for assessing PF. Major sonographic findings included increased plantar fascia thickness and hypoechoic plantar fascia. In addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Based on the research, X-rays are useful diagnostic techniques for excluding acute osseous abnormalities, such as calcaneal stress fractures, that might cause heel discomfort [7]. Moreover, an MRI can help rule out other pathologies in cases with unusual or resistant heel pain, such as calcaneal edema, plantar fascia tears, or arteriovenous malformations [18]. Differential diagnosis of PF can be conducted from aspects of skeletal orign, soft tissue orign, and neurogenic orign [1].…”
Section: Imaging Examination and Differential Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the research, X-rays are useful diagnostic techniques for excluding acute osseous abnormalities, such as calcaneal stress fractures, that might cause heel discomfort [7]. Moreover, an MRI can help rule out other pathologies in cases with unusual or resistant heel pain, such as calcaneal edema, plantar fascia tears, or arteriovenous malformations [18]. Differential diagnosis of PF can be conducted from aspects of skeletal orign, soft tissue orign, and neurogenic orign [1].…”
Section: Imaging Examination and Differential Diagnosismentioning
confidence: 99%
“…After using a pressure meter, heel pain was reduced to excellent or good, and the visual analog scale (VAS) score was lowered by 60% throughout everyday activities and the first step of the morning [24]. In addition, a network meta-analysis comprising 19 trials demonstrated that ESWT significantly reduced pain in the short term (<6 weeks) and intermediate term (2-4 months) when compared to placebo [18]. According to another recent RCT, patients with thinner plantar fascia reported less pain following ESWT, and both the highintensity (0.56 mJ/mm2) and low-intensity (0.12 mJ/mm2) groups showed comparable improvements in pain and function [18].…”
Section: Extracorporeal Shock Wave Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the diagnosis of this chronic degenerative process is simple and clinical, a differential diagnosis with other pathologies (skeletal origin, soft tissue origin, or neurogenic origin) needs to be carried out in order to provide adequate treatment. The diagnosis is based on the patient’s symptoms, and after 8 weeks of pain it is to be considered chronic PF; this is also the case if the ultrasound image shows a degenerate, hypoechogenic (low brightness intensity of the image of the plantar fascia related to ultrasound waves and associated with pain), and thick fascia [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are different treatment modalities for plantar fasciitis that must be taken into account in the therapeutic treatment plan, starting with conservative measures and ending with long-term surgical management, such as Achilles’ lengthening [ 3 ]. The conservative treatments are the first option, and these include plantar orthoses [ 4 , 5 ], muscle stretching [ 6 , 7 ], functional taping [ 8 ], radial extracorporeal shockwave therapy (rESWT) [ 9 , 10 , 11 ], laser therapy [ 12 ], systemic pharmacological therapy [ 13 ], and percutaneous injection [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%